Healthcare interventions for sex workers: protocol for a scoping review - Eleanor Molloy; Julie Taylor; Joht Singh Chandan; Nutmeg Hallett; Caroline Bradbury-Jones; Sara Croxford; Christine Christie; Jack Docherty-Smith; Heather Welborn; Hannah Wright (BMJ Open, 2023)
Introduction Sex workers, who provide sexual or erotic acts in exchange for payment, often experience multiple disadvantages, including mental ill health and substance misuse. Mainstream healthcare services are generally not configured to facilitate engagement with sex workers and therefore, services are needed that are accessible to this population. The aim of this scoping review is to understand the evidence base for approaches, services and interventions that are aimed at addressing sex workers’ health needs.Methods and analysis Nine databases, CINAHL, Embase, EThOS, Google Scholar, Health Management Information Consortium, MEDLINE, ProQuest Dissertations and Theses, PsycINFO and Web of Science (Core Collection), will be searched, with results limited to English language publications and those published from 2003 onwards. De-duplication, study selection and data extraction will be conducted using Covidence software. Included studies will describe or evaluate approaches, services or interventions that address the health needs of sex workers who offer services that involve physical contact with a client.Ethics and dissemination No ethical review is needed. The final report will be shared with Birmingham City Council as part of ongoing work and will be disseminated by peer-reviewed publication.Study registration Open Science Framework (doi: 10.17605/OSF.IO/N7WSX).